Penerapan Personal Hygiene, Sanitasi Peralatan, dan Sanitasi Lingkungan pada Pedagang Nasi Goreng: Studi Kasus Pada Pedagang Nasi Goreng di Kota Balikpapan - Dianovita, Chardina; Gardiarini, Praseptia; Farida, Farida; Agung, Yolinda (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2024)
The importance of maintaining cleanliness and health is carried out to avoid the dangers of pollution and contamination and prevent various types of diseases. The purpose of this study was to describe personal hygiene, equipment sanitation, and environmental sanitation for fried rice seller. The type of research used is descriptive qualitative, using data collection methods through field observations, in-depth interviews, and the results of documentation. The respondents used were Artomoro fried rice seller who had at least 3 months work experience and were directly involved in handling food. Based on the results of observations, it was found that employees had not properly implemented personal hygiene, such as not using aprons, gloves and head coverings. For the use of equipment is good enough, and store equipment in a clean place. In the selling area, trash is still scattered on the terraces of the stalls, moldy walls and trash cans with open conditions, but trash bins are routinely cleaned by changing the plastic waste every day.